2018
DOI: 10.1159/000494260
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Sex-Specific Characteristics of Nicotine Addiction Using Metabolic and Structural Magnetic Resonance Imaging

Abstract: Nicotine addiction is known to modulate neurotransmission and alter the brain structure. The detrimental effect of nicotine is more prominent in females as compared to males. This study sought to examine the sex-specific influence of nicotine addiction on gamma amino butyric acid (GABA) and the white matter (WM) microstructure. Sixty healthy subjects (smokers/non-smokers) underwent structural and metabolic magnetic resonance imaging scans. Results showed alterations in WM integrity (measured as changes in frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…First and foremost, the sample size of the study is relatively small, which may reduce the strength of our results. Secondly, previous studies have shown gender and racial differences in brain function in smokers (Bagga et al, 2018;McCarthy et al, 2019;Lin et al, 2021). The participants included in the current study were all Chinese males, so the results of this study may not account for all smokers.…”
Section: Discussionmentioning
confidence: 87%
“…First and foremost, the sample size of the study is relatively small, which may reduce the strength of our results. Secondly, previous studies have shown gender and racial differences in brain function in smokers (Bagga et al, 2018;McCarthy et al, 2019;Lin et al, 2021). The participants included in the current study were all Chinese males, so the results of this study may not account for all smokers.…”
Section: Discussionmentioning
confidence: 87%
“…The participants received 20 EUR as compensation for their time. Some parts of this section have been adapted from another study by the same authors due to similarities in the recruitment pipeline [33]. Self-Reported Questionnaire Assessment All participants were administered a set of questionnaires at the beginning of the study, namely, the Leiden Index of Depression severity (LEIDS-R: measures vulnerability to depression [34]), the Frankfurter Aufmerksamkeits Inventar (FAIR: performance test for concentration and focused attention; [35]), and the Standard Progressive Matrices (SPM: intelligence test, investigating the participants' ability to find meaning in complex schemata and recall the necessary information for this [36]).…”
Section: Study Participantsmentioning
confidence: 99%
“…They reported that lower dACC GABA was associated with heightened reactivity to drug cues and more withdrawal symptoms, which suggests that GABA is related to dependence severity [ 74 ]. In the prefrontal cortex, female smokers ( n = 15) had significantly higher levels of GABA compared to female non-smokers ( n = 15), and female smokers had lower GABA than male smokers ( n = 15) [ 73 ]. There was no difference in GABA between male smokers and non-smokers ( n = 15) [ 73 ].…”
Section: Gabaergic Alterations In Drug Addictionmentioning
confidence: 99%
“…In the prefrontal cortex, female smokers ( n = 15) had significantly higher levels of GABA compared to female non-smokers ( n = 15), and female smokers had lower GABA than male smokers ( n = 15) [ 73 ]. There was no difference in GABA between male smokers and non-smokers ( n = 15) [ 73 ]. In a male-only nicotine and polysubstance use population, one study found no significant difference in GABA between current smoking males ( n = 48), current smoking and polysubstance use males ( n = 61), and healthy control ( n = 90) [ 81 ].…”
Section: Gabaergic Alterations In Drug Addictionmentioning
confidence: 99%